2021
DOI: 10.1111/joa.13585
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometry of mast cells in the convexity of human intracranial dura mater

Abstract: The intracranial dura mater is a thick meningeal barrier of connective tissue located between the skull and leptomeninges. This meninx can be divided into three layers: the periosteal (external), the meningeal (internal), and the subdural neurothelium. Such layers are well joined, separated only in the venous sinuses and the cerebral falx (Haines, 1991).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Recently, we described the histomorphometric aspects of mast cells located in the convexity of the human dura mater. 8 We observed that the mast cells are located close to blood vessels, with a more significant number of cells next to the venous vessels of the periosteal layer and in the proximal region of the superior sagittal sinus. 8 Different from rat (with two), three distinctive dural layers (periosteal, meningeal, and dural border cell layers) are identified in the human dura mater, with a thickness of 564 ± 50 µm.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Recently, we described the histomorphometric aspects of mast cells located in the convexity of the human dura mater. 8 We observed that the mast cells are located close to blood vessels, with a more significant number of cells next to the venous vessels of the periosteal layer and in the proximal region of the superior sagittal sinus. 8 Different from rat (with two), three distinctive dural layers (periosteal, meningeal, and dural border cell layers) are identified in the human dura mater, with a thickness of 564 ± 50 µm.…”
Section: Discussionmentioning
confidence: 61%
“…8 We observed that the mast cells are located close to blood vessels, with a more significant number of cells next to the venous vessels of the periosteal layer and in the proximal region of the superior sagittal sinus. 8 Different from rat (with two), three distinctive dural layers (periosteal, meningeal, and dural border cell layers) are identified in the human dura mater, with a thickness of 564 ± 50 µm. 12 The cells are slightly erratically oriented in the periosteal and meningeal layers.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation